Metode Reward dan Punishment : Solusi Tepat dalam Meningkatkan Motivasi Belajar Siswa - Kasrina, Ela (Institut Agama Islam Negeri Kediri, 2023)
Abstract: This study aims to understand the optimization of Reward and Punishment methods in increasing student learning motivation. The research approach employed here is qualitative, specifically the Classroom Action Research (CAR) method. Data were obtained through observation, interviews, and tests from 15 students at SMPN 5 Palakka. Data analysis techniques encompassed data reduction, data presentation, and drawing conclusions. The research results indicate that there is an improvement in student motivation through the optimization of reward and punishment methods. Two indicators are associated with this improvement, namely, student perseverance in learning and their interest in participating in the learning process. Both of these aspects can be enhanced through the forms of rewards provided by the teacher. For instance, teacher applause followed by the entire class, complimentary snacks for students who achieve learning targets, and cumulative grade-based rewards until the final report card. Additionally, the forms of punishment implemented also contribute to heightened motivation, such as classmates' encouraging shouts or academic punishments like individual recitations of the Asmaul Husna and short surahs in front of the class. It's worth noting that no physical punishments were administered by the teacher. These reward and punishment mechanisms have proven to be effective, as evidenced by a 35% increase in student motivation in the first cycle and a 70% increase in the second cycle. Abstrak: Penelitian ini bertujuan untuk memahami optimalisasi metode Reward dan Punishment dalam meningkatkan motivasi belajar siswa. Pendekatan penelitian ini adalah pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas. Data diperoleh melalui teknik observasi, wawancara dan tes dari subyek penelitian sebanyak 15 siswa di SMPN 5 Palakka. Teknik analisa data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa ada peningkatan motivasi belajar melalui optimalisasi metode reward dan punishment. Ada dua indikasi terkait peningkatan motivasi, yakni ketekunan belajar siswa dan minat siswa dalam mengikuti pembelajaran. Kedua hal tersebut bisa meningkat karena bentuk reward yang diberikan oleh guru pada siswa, seperti tepukan tangan guru yang diikuti oleh seluruh siswa, snack yang diberikan secara cuma-cuma bagi siswa yang mampu mencapai target pembelajaran hingga reward nilai yang diakumulasi hingga nilai akhir dalam rapor. Selain itu, bentuk punishment yang diberikan juga mampu meningkatkan motivasi mereka, seperti teriakan ‘hu….’ dari teman-teman lainnya ataupun bentuk punishment akademis, seperti menghafal asmaul husna dan surat-surat pendek secara individu didepan kelas. Tidak ada hukuman fisik yang diberikan oleh guru. Bentuk reward dan punishment ini terbukti efektif, terlihat pada adanya peningkatan motivasi siswa sebesar 35% di siklus I dan 70% di siklus II.